Precise duty-cycle measurement for time of transit ultrasound flowmeters - Reis, S. (2010)
This article describes an ultrasound liquid flowmeter and a system for the measurement of the time of transit. The flowmeter is manufactured from a piezoelectric polymer such as -PVDF, in which one electrode in the inside and three electrodes in the outer side are placed. One of the exterior electrodes is excited by an electric voltage, whose frequency of 33 kHz, produces mechanical oscillations in the area of the pipe in contact with it, producing ultrasounds with the same frequency. The areas of the pipe under the other two electrodes also work as ultrasound transducers, receiving the signal produced by the first one. In the time of transit flowmeters, the phase differences between the emitted and received signals are used to calculate the speed of the flow inside the pipe. The phase differences between the emitted signal and the received ones appear as two signals of 33 kHz, whose duty-cycle changes according to the flow speed. So, a precise duty-cycle measurement technique, like the one demonstrated in this article, is necessary to correctly calculate the flow quantity.